Peningkatan Pengetahuan Perawat tentang Oral Hygiene di Ruang Rawat Inap HCU Penyakit Dalam RSUP Dr. M. Djamil Padang - Yuanita Ananda; Yulastri Arif; Zifriyanthi Minanda Putri; Esthika Ariany Maisa; Dewi Murni; Sidaria Sidaria; Ilfa Khairina; Muthmainnah Muthmainnah; Susmiati Susmiati; Nelwati Nelwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Personal hygiene is a person's effort to maintain cleanliness and health. One of the activities during morning care regarding patient personal hygiene that nurses often forget is performing oral hygiene. The results of interviews conducted with the patient's family indicated that oral hygiene treatment was rarely carried out. Therefore, it was necessary to provide education to increase nurses' knowledge about oral hygiene—the activity aimed at helping nurses to understand the importance of performing oral hygiene care. The implementation of the activity was carried out directly by the nurse by conducting a pre-test, giving material, and ending with a post-test. The results of the pre-test were the level of knowledge of nurses about oral hygiene care before being given education; namely, seven families had good knowledge (23%), ten families had sufficient knowledge (33%), and 13 families had poor knowledge (44%). The post-test results were the family knowledge level in the HCU Internal Medicine ward at RSUP Dr M. Djamil Padang after being given education; 25 families had good knowledge (83%), and five families had sufficient knowledge (17%). Based on these results, the educational activity was beneficial, can increase nurses' knowledge about oral hygiene care, and can be applied directly to patients. The suggestion is that nursing managers can control oral hygiene care to optimize nursing services.